PARAPELVIC CYST MAY CONCEAL URETEROPELVIC JUNCTION OBSTRUCTION - Tufek, I; Argun, B.; Keskin, S.; Akpinar, H.; Atug, F.; Kural, A. R. (WILEY-BLACKWELL, 2012)
EAU Robotic Urology Section Congress (ERUS), London, ENGLAND, SEP 26-28, 2012